2002
DOI: 10.1037/0893-164x.16.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of alcohol measures: Is there a difference between Internet-based assessment and traditional methods?

Abstract: This study compared Web-based assessment techniques with traditional paper-based methods of commonly used measures of alcohol use. Test-retest reliabilities were obtained, and tests of validity were conducted. A total of 255 participants were randomly assigned to 1 of 3 conditions: paper-based (P&P), Web-based (Web), or Web-based with interruption (Web-I). Follow-up assessments 1 week later indicated reliabilities ranging from .59 to .93 within all measures and across all assessment methods. Significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(174 citation statements)
references
References 24 publications
(32 reference statements)
6
165
0
3
Order By: Relevance
“…Although accuracy of self-report measures has been questioned, evidence suggests that college student self-report is both reliable and valid (Babor et al, 2000;Miller et al, 2002). It is also possible that assessing drinking plans before the celebration infl uenced behaviors during the celebration.…”
Section: Discussionmentioning
confidence: 99%
“…Although accuracy of self-report measures has been questioned, evidence suggests that college student self-report is both reliable and valid (Babor et al, 2000;Miller et al, 2002). It is also possible that assessing drinking plans before the celebration infl uenced behaviors during the celebration.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy drinking was defined as four or more drinks in an occasion for a woman and five or more drinks in an occasion for a man . E. T. Miller et al (1998) found high (r ϭ .93) 1-week test-retest correlations for the DDQ estimate of drinks per week. Alcohol-related problems common to college students (e.g., missing class, getting into fights or arguments, driving after drinking) were assessed with the Rutgers Alcohol Problem Inventory (RAPI), a reliable and internally consistent (Borsari & Carey, 2000) instrument that accurately discriminates between young adults with and without a Diagnostic and Statistical Manual of Mental Disorders (3rd ed., rev.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, both online questionnaires (Miller et al, 2002) and the handheld devices utilized in the groups (LaBrie et al, 2006) have both been shown to be comparable to traditional paper and pencil self-report questionnaires. Nevertheless, there are no studies to date which directly compare online measurements of alcohol use and attitudes with the handheld device system.…”
Section: Limitationsmentioning
confidence: 99%
“…Participants were sent an online assessment survey to their campus email addresses (Time 1). As online means of collecting data from participants are becoming increasingly common, Miller et al (2002) found no differences between webbased assessment of alcohol use and traditional paper and pencil reports. Before entering the survey, participants had to electronically "sign" the university IRB-approved consent form.…”
Section: Design and Proceduresmentioning
confidence: 99%